K-shell ionization cross section of Ti and Cu atoms by 1 and 2 GeV electrons. (25th February 2021) - Nazhmudinov, R M; Shchagin, A V; Trofymenko, S V; Kishin, I A; Kubankin, A S; Potylitsyn, A P; Gogolev, A S; Filatov, N A; Kube, G; Potylitsina-Kube, N A; Stanitzki, M; Novokshonov, A
Abstract: The K -shell ionization cross sections of titanium and copper atoms were determined by analyzing the spectra of characteristic X-ray radiation generated by an electron beam with energies of 1 and 2 GeV in metal foils. New data obtained for these energies demonstrate the influence of the density effect on the ionization cross sections values. The results were compared with previous experimental data and calculations based on pure theoretical and semi-empirical models.